Frontiers of ctDNA, targeted therapies, and immunotherapy in non-small-cell lung cancer - Zhu, Chennianci (Transl Lung Cancer Res, 2020)
Non-small-cell lung cancer (NSCLC), a main subtype of lung cancer, is one of the most common causes of cancer death in men and women worldwide. Circulating tumor DNA (ctDNA), tyrosine kinase inhibitors (TKIs) and immunotherapy have revolutionized both our understanding of NSCLC, from its diagnosis to targeted NSCLC therapies, and its treatment. ctDNA quantification confers convenience and precision to clinical decision making. Furthermore, the implementation of TKI-based targeted therapy and immunotherapy has significantly improved NSCLC patient quality of life. This review provides an update on the methods of ctDNA detection and its impact on therapeutic strategies; therapies that target epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) using TKIs such as osimertinib and lorlatinib; the rise of various resistant mechanisms; and the control of programmed cell death-1 (PD-1), programmed cell death ligand-1 (PD-L1), and cytotoxic T-lymphocyte antigen-4 (CTLA-4) by immune checkpoint inhibitors (ICIs) in immunotherapy; blood tumor mutational burden (bTMB) calculated by ctDNA assay as a novel biomarker for immunotherapy. However, NSCLC patients still face many challenges. Further studies and trials are needed to develop more effective drugs or therapies to treat NSCLC.